Designer's guide to eurocode 9 design of aluminium structures EN 1999-1-1 and -1-4 - Hoglund, Torsten (Eurocode designer's guide series, 2012)
Eurocode 9 covers the design of building and civil engineering works made from wrought and cast aluminium alloys. While aluminium is a lesser-used material, EN9 is a complicated document and there is currently very little guidance to its use. The latest addition to the bestselling Designers' Guide series addresses the considerable demand for Eurocode guidance covering aluminium. Designers' Guide to Eurocode 9 is written by 3 authorities on the subject, who were instrumental in drafting the original code and contains worked examples throughout.